Identify the Types of Grass in the Lembah Dieng Area, Malang Regency, East Java - Lestari, Aninda Ayu; Ramadhani, Devita Ayu; Azmi, Difa' Isabitul; Saputri, Nana Yuliana; Puspitasari, Noviana; Fardhani, Indra (Jurnal Biologi Tropis, 2024)
The study aims to identify the kinds of grass that grow in the Lembah Dieng Area, Malang Regency. Field surveys are conducted to record and collect data on distribution and types of grasses. The mapping was done using direct survey techniques and sample retrieval. Research has shown that the region's ungutted wedges have significant variations in the composition and distribution of grass. There are a number of species of grass that have been found, including common types and some relatively rare species. Data analysis lists environmental factors that affect the growth and distribution of grasses in this region. The information gathered from this study is hoped to provide a better understanding of the diversity of grasses in the region's wedges, which can be useful for the management of agricultural land and the conservation of natural resources in the region.